Analysis of concept construction errors in mathematical problem solving based on the assimilation and accommodation framework in terms of student learning styles - Putri, Yeni; Huda, Nizlel; Yantoro, Yantoro (Universitas Islam Negeri Raden Intan Lampung, 2021)
The forms of concept construction errors are divided into 4 forms, namely (1) Pseudo Construction, (2) Construction Holes, (3) Mis Analogical Construction, (4) Mis Logical Construction. This research aims to determine the process of concept construction errors in solving mathematical problems based on the assimilation and accommodation framework in terms of student learning styles. This research is qualitative descriptive research. The results showed that 1) students with visual learning styles experienced True Pseudo Construction, False Pseudo Construction, and Construction Pits. 2) Students with auditory learning styles experience True Pseudo Construction, False Pseudo Construction as well as Construction Pits and Mis Logical Construction. 3) Students with kinesthetic learning styles experience Construction Pits, True Pseudo Construction, False Pseudo Construction, and Mis Logical Construction. Concept construction errors in the material of a System of Linear Equations with Three Variables that are often experienced by students are Construction Pits caused by students' spontaneous thinking, irregularity of students' knowledge from previous knowledge concepts with new knowledge concepts.